Comparison of Behavior-Related Features in the MMSE Sentence in Behavioral Variant Frontotemporal Dementia and Alzheimer’s Disease - Ruiz-Garcia, Ramiro; Yu, Soojung; Richardson, Lauryn; Roberts, Angela; Pasternak, Stephen; Stewart, Chloe; Finger, Elizabeth (Frontiers in Aging Neuroscience, 2021)
Background: Characterization of unscored behavior-related features of the MMSE sentence item may assist in identification of patients with behavioral variant Frontotemporal Dementia (bvFTD) in comparison to Alzheimer’s disease (AD). Objective: To describe and compare the unscored content and grammar elements of the MMSE sentence item in patients with bvFTD and AD. Methods: Categorization of predefined content and grammar elements of the MMSE sentence was performed by two blinded raters in patients with bvFTD (n = 74) and AD (n = 84). Chi-square and ANCOVAs were conducted to identify differences between the diagnostic groups. A multinomial logistic regression analysis was then conducted to determine whether these features aid in the prediction of diagnosis of bvFTD or AD. Results: A higher proportion of patients with bvFTD wrote sentences addressed to the examiner (22.7% vs 4.7%, X2=11.272, p=0.001) and about interpersonal relationships (35.3% vs 16.0%, X2=10.139, p=0.017) in comparison to those with AD. The number of words written was lower in patients with AD and was positively correlated with lower total MMSE scores in AD but not in bvFTD (r=0.370, CI 95% 0.197 – 0.506, p<0.001). Assessment of the MMSE sentence content and grammar variables did not add to the prediction bvFTD or AD diagnosis beyond the variance explained by age and total MoCA score. Conclusions: Patients with bvFTD and AD showed differences in aspects of content of the written MMSE sentence item, though these differences did not aid in the prediction of bvFTD and AD diagnosis.